IDENTIFIKASI UNSUR-UNSUR KIMIA PADA KAYU KERAS (HARDWOOD) DAN KAYU LUNAK (SOFTWOOD) DENGAN TEKNIK LASER INDUCED SHOCKWAVE PLASMA SPECTROSCOPY - Dani Rustanti; Mangasi Alion Marpaung; Maria Margaretha Suliyanti (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Spectral analysis of elemental wood samples (teak, meranti and balsa) has been done using Laser Induced Shockwave Plasma Spectroscopy with laser Nd-YAG (1064 nm, 10 Hz), which is operated in mode Q-Switch. The study was conducted to identify and compare the content of the chemical elements of the wood samples. Samples were placed in a chamber made of metal where the air pressure can be varied with vacuum pumps. In this experiment there are three times varied pressure 5 torr, 15 torr and 35 torr while the laser energy is varied 5 times, which are 12 mJ, 45 mJ, 70 mJ, 93 mJ, and 120 mJ. Plasma generated by focusing the beam (pulse) of  laser at the sample surface by the focusing lens through the window. Plasma radiation was detected using a spectrometer equipped with fiber optics. The research results obtained spectrum plasma lines are the sharpest on the energy of 93 mJ pressure of 5 torr for each samples. The elements were detected, namely carbon (C), hydrogen (H), oxygen (O), calcium (Ca), nitrogen (N), magnesium (Mg), and potassium (K) which the intensity of the hardwood elements (teak and meranti) is higher than the intensity of the softwood elements (balsa).Keywords: Laser Induced Shockwave Plasma Spectroscopy, hardwoods and softwoods, identification of                                          chemical elements.